Redefining landmarks - Lamit, Hasanuddin (2007, 2007)
Paths, nodes, districts, landmarks and edges as classified by Kevin Lynch have been strongly debated since the 1960’s and the typical issue of contentment would be about the overlapping definitions between some categories and their order of importance. For example, can a node be a landmark? Some commentators consider that landmarks are one of the most significant urban components and possibly more important than other components that require examination and appraisal. This paper will discuss if landmarks can be perceived beyond their archetypal perception of being tall, large, monumental, distinct, and referring only to buildings or towers. It is the aim of the study to expand the notion of landmarks into several categories.